THE EFFECT of ANIONIC SORPTION on THE METAKAOLINITE - Campos, Valquiria [UNESP]; Morais, Leandro C. [UNESP]; Rosa, Andre H. [UNESP]; Fraceto, Leonardo F. [UNESP]; Buchler, Pedro M. (Trans Tech Publications Ltd, 2010)
This paper reports an investigation on the effect of thermal activation of kaolinite. It is well known that during calcinations (400-650 degrees C), kaolinite loses the OH lattice water and is transformed into metakaolinite or amorphous material. Arsenic is trace element that is toxic to animals including humans. The adsorption of arsenic on kaolinite was investigated at varying pH and thermal pretreatment. Calcination of sample is carried out at 650 degrees C for 3 h. The decomposition of kaolinite is recorded using methods of thermal analysis. The resultant product is identified by XRD. Laboratory experiments were conducted examining the effect of arsenic by thermally modified kaolinite. The Langmuir isotherm was used to describe arsenite and arsenate sorption by the calcined kaolinite. The equilibrium parameters used were based on experimental data obtained for the dynamic adsorption process of arsenic. Removal of arsenate using natural kaolinite was satisfactory, whereas arsenic was not removed by adsorption with thermally modified kaolinite. Moreover, the adsorption of arsenic by kaolinite and metakaolinite decreases with increasing pH.
Keywords: natural kaolinite; thermal treatment; removal; anion; water